2007
DOI: 10.1007/s00125-006-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the neuropeptide Y2 receptor (NPY2R) gene and association with severe obesity in French white subjects

Abstract: Aims/hypothesis Genetic variants of genes for peptide YY (PYY), neuropeptide Y2 receptor (NPY2R) and pancreatic polypeptide (PPY) were investigated for association with severe obesity. Subjects and methods The initial screening of the genes for variants was performed by sequencing in a group of severely obese subjects (n=161). Case-control analysis of the common variants was then carried out in 557 severely obese adults, 515 severely obese children and 1,163 nonobese/non-diabetic control subjects. Rare variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 54 publications
4
30
0
Order By: Relevance
“…The frequencies of the examined genotypes were similar to the previously analyzed populations in AHSG [ 4 , 7 , 8 ] , HCRT [ 18 ] and NPY2R [ 1 , 21 , 23 ] . The number and percentage of individual genotypes and call rates are summarized in Table 3 .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The frequencies of the examined genotypes were similar to the previously analyzed populations in AHSG [ 4 , 7 , 8 ] , HCRT [ 18 ] and NPY2R [ 1 , 21 , 23 ] . The number and percentage of individual genotypes and call rates are summarized in Table 3 .…”
Section: Resultssupporting
confidence: 83%
“…These abdominal hormones are members of the pancreatic polypeptide family together with pancreatic polypeptide (PP). All these polypeptides have been described as strong central regulators of gastric function [ 1 , 21 ] . Neuropeptide Y is an appetite hormone and is widely distributed throughout the central and peripheral nervous systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Unfortunately, PYY secretion was not assessed in these studies, but it is possible that these polymorphisms might lower PYY secretion. These findings support our results and hypothesis that a disturbed PYY release could be part of a primary hereditary defect, promoting the further development of obesity and T2D.…”
Section: Blunted Pyy Response In Prediabetes a Viardot Et Almentioning
confidence: 99%
“…Ma et al (28) found that obesity was predicted by two PYY genetic variants in Pima Indian men. Siddiq et al (29) found association of an intronic PYY variant with childhood obesity but not in adults in a European sample. However, the mechanism whereby PYY genetic variation influences metabolic syndrome traits has remained elusive.…”
Section: Contextmentioning
confidence: 97%